Designing web accessibility for a beautiful web - Clarke, Andy, 1965-; Sweeney, Mary (New Riders, 2009)
"In Transcending CSS: The Fine Art Of Web Design (New Riders), renowned designer and author Andy Clarke set the stage for the development of progressive Web site design using XHTML, CSS and other Web-standards technologies. In this new video, Andy picks up one of the more challenging aspects of Web design: making sites accessible to as wide an audience as possible while still maintaining a solid design aesthetic. In the video, Andy shows how using a modern workflow, which includes designing using a web browser, eliminates common accessibility problems. Readers will learn how to design accessible content as well as write accessible HTML and XHTML markup and CSS. They will also learn key business benefits of creating an accessible site, including more value for money spent on design and better search engine placement. Throughout the video, Andy demonstrates these concepts using examples from a fictitious social networking site he created."--Resource description page